Striatal Spine Plasticity in Parkinson's Disease - Villalba, Rosa M.; Smith, Yoland (Frontiers in Neuroanatomy, 2010)
Striatal dopamine (DA) denervation results in a significant loss of dendritic spines on medium spiny projection neurons in Parkinson's disease. In 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine-treated parkinsonian monkeys, spines contacted either by cortical or thalamic glutamatergic terminals are severely affected on both direct and indirect striatofugal neurons. In rodents, indirect pathway neurons appear to be more sensitive, at least in early stages of acute dopamine denervation. The remaining corticostriatal and thalamostriatal axo-spinous synapses undergo complex ultrastructural remodeling consistent with increased synaptic activity in the DA-denervated primate striatum, which may explain the pathophysiological overactivity of the corticostriatal system reported in various animal models of parkinsonism. The calcium-mediated regulation of the transcription factor myocyte enhancer factor 2 was recognized as a possible underlying mechanism for striatal spine plasticity. Future studies to determine how alterations in striatal spine plasticity contribute to the symptomatology of parkinsonism are warranted.